GAYA BAHASA DALAM ANTOLOGI CERPEN CINTA DI ATAS PERAHU CADIK KARYA SENO GUMIRA AJI DHARMA - Ummamah ainun Jariyah, Binti (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aimed to describe the stylistic comparisons and contradictions in the short story anthology â€œCinta di Atas Perahu Cadikâ€. To determine the style of the language in the short story anthology â€œCinta di Atas Perahu Cadikâ€ which consists of fifteen short stories, researchers studying style by using the theory of Henry Guntur Tarigan. In accordance with the objectives to be achieved in this study, the research approach used is descriptive qualitative approach. Having done the research study style in the short story